2002
DOI: 10.1002/jso.10116
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic arterial infusion of 5‐fluorouracil and cisplatin for unresectable or recurrent hepatocellular carcinoma with tumor thrombus of the portal vein

Abstract: The chemotherapy described in this report is beneficial in terms of survival for HCC patients with PVTT for whom transcatheter arterial embolization or surgical treatment is contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 17 publications
0
59
0
Order By: Relevance
“…Recently, some authors reported that even patients with liver cirrhosis were treated effectively with TAI (cisplatin and 5-fluorouracil). 10,11 Moreover, interferon ␣ was added to TAI to augment the cytotoxic effects. 32,33 In those studies, the objective response rates were 33-73%; the overall survival rates at 1 years and 2 years were 24 -45% and 15-31%, respectively; and the median survival was 7.5-10.2 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, some authors reported that even patients with liver cirrhosis were treated effectively with TAI (cisplatin and 5-fluorouracil). 10,11 Moreover, interferon ␣ was added to TAI to augment the cytotoxic effects. 32,33 In those studies, the objective response rates were 33-73%; the overall survival rates at 1 years and 2 years were 24 -45% and 15-31%, respectively; and the median survival was 7.5-10.2 months.…”
Section: Discussionmentioning
confidence: 99%
“…6,10,11,32,33,[42][43][44][45] Furthermore, 75% of the patients in the current series had bulky tumors that measured Ն 50 mm in greatest dimension. This result suggests that proton beam therapy alone can be a curative modality of treatment for patients who have HCC with PVTT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HAIC appears to deliver high concentrations of chemotherapeutic agents to HCC tissues selectively, with low toxicity for non-cancerous liver tissues and the whole body. Several reports described the effects of HAIC with cisplatin and 5-FU or systemic interferon-α therapy with HAIC using 5-FU for HCC patients with tumor thrombosis in the first branches and the portal vein trunks (21,45). Therefore, we showed that NFP is more effective than sorafenib therapy in patients with advanced HCC and MVI.…”
Section: Discussionmentioning
confidence: 58%